(untitled) (Research, Society and Development, 2021)
Objective: to show how the antioxidant mechanisms occur in the human body and to investigate the parameters of oxidative stress and its relationship with physical exercise, revealing researches that indicate ways to avoid this process, trying to prevent diseases that appear with the inadequate exercise practice. Methods: the study is a literature review on oxidative stress associated with exercise, according to the author’s own interpretation and critical analysis. Such research method involves the synthesis of articles already published, allowing the construction of the analysis of the scientific literature. The databases used for the search were Bireme, medline, Scientific Electronic Library Online (SciELO) and Pubmed. Results: The results show that the regular practice of physical exercises associated with good eating habits influences in reducing the prevalence of metabolic syndrome and increasing the concentration of glutathione and the total antioxidant protection. Conclusion: intense and exhausting physical exercises promote an imbalance between oxidizing and antioxidant agents and are the most important factors in the formation of oxidative stress, the regular practice of physical exercises is considered a factor of great relevance in the modulation of oxidative stress.